ByzRev 06.2024.032: Florin Leonte, Ethos, Logos, and Perspective.: Studies in Late Byzantine Rhetoric (Routledge Research in Byzantine Studies). London – New York: Routledge 2023. - Valiavitcharska, Vessela (The Byzantine Review, 2024)
Florin Leonte, Ethos, Logos, and Perspective. Studies in Late Byzantine Rhetoric (Routledge Research in Byzantine Studies). London – New York: Routledge 2023. 229 pp. – ISBN 978-1-032-34336-5